Goppa and Srivastava codes over finite rings - Andrade, Antonio Aparecido de [UNESP] (2005)
Goppa and Srivastava codes over arbitrary local finite commutative rings with identity are constructed in terms of parity-cleck matrices. An efficient decoding procedure, based on the modified Berlekamp-Massey algorithm, is proposed for Goppa codes.